NOVEL CEPHALOSPORIN DERIVATIVE AND ANTIBACTERIAL AGENT - TSURUOKA TAKASHI; KATANO KIYOAKI; OGINO HIROKO; IWAMATSU KATSUYOSHI; YOSHIDA TAKASHI; KONDO SHINICHI; OKAMOTO RYOICHI; SEZAKI MASAJI (1987)
NEW MATERIAL:A cephalosporin derivative of formula I (R is 5-6-membered heterocyclic group or bicyclic hetero group containing N and optionally S and O and optionally having substituent group) having 2-( 2-aminothiazol-4-yl )-2-(1,5- dihydroxy-4-pyridone- 2-carboxamido) acetamido group at 7-site and its salt. EXAMPLE:(6R,7R)-7-[(RS)-2-(2-aminothiazo-4-yl)-2-(1,5-dihydroxy-4-pyri done-2-car boxamido) acetamido]- 3-(1-methyl-1H-tetrazol-5-yl) thiomethyl-ceph-3-em- 4- carboxylic acid. USE:Antibacterial agent against Gram-positive bacteria, Gram-negative bacteria and Pseudomonas aeruginosa. PREPARATION:The compound of formula II (R is H or amino-protecting group; R is H or carboxyl-protecting group) is made to react with the compound of formula III (R and R are H, benzyl, etc.).